2021
DOI: 10.17762/turcomat.v12i2.1808
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network in Convolution with Constant Error Carousel Based Long Short Term Memory for Better Face Recognition

Abstract: Unconstrained face identification, facial periocular recognition, facial land marking and pose prediction, facial expression recognition, 3D facial model design, and other facial-related problems require robust face detection in the wild. Despite the fact that the face recognition issue has been researched intensively for decades with different commercial implementations, it nevertheless faces problems in certain real-world scenarios due to multiple obstacles, such as severe facial occlusions, incredibly low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The calculation formula is shown in equation 3. 13. Next, a grid search method is used to systematically explore various combinations of hyper-parameters [17].…”
Section: Design Of An Intelligent Management System For Education Bas...mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation formula is shown in equation 3. 13. Next, a grid search method is used to systematically explore various combinations of hyper-parameters [17].…”
Section: Design Of An Intelligent Management System For Education Bas...mentioning
confidence: 99%
“…Self-channel attention was utilized to fuse feature maps in both channel and space. The experimental results showed that this face detection technology was superior to other face recognition models [13]. Sun et al proposed an English pedagogy model to enhance students' learning efficiency.…”
Section: Introductionmentioning
confidence: 95%
“…The experiments show that the RSCPA algorithm can obtain sparser vectors with the same performance as the PCA algorithm, demonstrating the superiority of the algorithm in face recognition and handwritten digit recognition [2].Ramaraj P To address severe facial occlusions, incredibly low resolution, strong illumination, unusual pose inconsistencies, picture or video compression artefacts, etc., it is in some realistic scenarios still face problems,adaptively aggregated channel and spatial domain Self-Confident Channel Attention (SCA) blocks and Self-Spatial Attention (SSA) blocks are used, followed by the Canny Kirsch method edge detection algorithm to identify face edges. Experimental results show that the proposed method outperforms the current state-of-the-art face recognition methods [3]. All of the above-mentioned technical approaches have shown different kinds of shortcomings in the face of the special circumstances of epidemic prevention and control, and are unable to meet the needs of face recognition at present.…”
Section: Introductionmentioning
confidence: 96%